PENINGKATAN MINAT BELAJAR ANAK USIA DINI MELALUI PEMBELAJARAN BERBASIS PROYEK - Alfajri Husain, Itsnain; Satrianta, Hengki (Program Studi PG PAUD Universitas PGRI Ronggolawe, 2025)
Learning interest was something that must be possessed by early childhood in their learning activities. In reality, it was found that early childhood was still unable to develop their learning interest. It is necessary to see whether the project-based learning method has a different impact on children's learning interest or there was no different impact. The purpose of this study was to determine whether the learning interest in children in Kelompok B TK Seruni Desa Taore Kecamatan Aere Kabupaten Kolaka Timur can be improved through project-based learning. This study is a quantitative study with an experimental type. This study was conducted in Kelompok B TK Seruni Desa Taore Kecamatan Aere Kabupaten Kolaka Timur. The sample in this study was 24 children who were drawn using the total sampling technique from the research population of 24 children. Data were collected through observation techniques and performance tests. Data were analyzed descriptively to describe the research data. In addition, hypothesis testing was carried out using the Wilcoxon test. The results of the study showed that children's learning interest in Kelompok B TK Seruni Desa Taore Kecamatan Aere Kabupaten Kolaka Timur can be improved through project-based learning. The implication of the results of this study is that teachers at the early childhood education level can use this learning method to develop children's learning interest.